(untitled) (Revista Archai, 2019)
In this paper, I defend that the historiographical category of eclecticism is a correct way to describe the epistemology and the exegetical activity of the Anonymous commentator on Plato’s Theaetetus. In addition, I show that the interpretation of the platonic philosophy presented in this text not only presupposes an eclectic philosophical attitude, but also offers a conscious defense of a positive and philosophically relevant form of eclecticism. By eclecticism, I understand a method of inquiry based on the deliberate use of hypotheses and arguments from different philosophical traditions. My claim is that Anon. intends to lay ground of his way of doing philosophy by attributing it to Plato and the platonic tradition. In doing so, Anon. provides us with a positive understanding of eclecticism as a legitimate methodology of philosophical investigation.